Interaction of lipoprotein lipase polymorphisms with body mass index and birth weight to modulate lipid profiles in children and adolescents: the CASPIAN-III Study - Askari, Gholamreza; Heidari-Beni, Motahar; Mansourian, Marjan; Esmaeil-Motlagh, Mohammad; Kelishadi, Roya (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Interactions between body mass index (BMI), birth weight and risk parameters may contribute to diseases rather than the individual effects of each factor. However this hypothesis needs to be confirmed. This study aimed to determine to what extent variants of lipoprotein lipase (LPL) might interact with birth weight or body weight in determining the lipid profile concentrations in children and adolescents. DESIGN AND SETTING: Substudy of the third survey of a national surveillance system (CASPIAN-III Study) in Iran. METHODS: Whole blood samples (kept frozen at -70 °C) were randomly selected from 750 students aged 10-18 years. Real-time polymerase chain reaction (PCR) and high-resolution melt analysis were performed to assess S447X (rs328), HindIII (rs320) and D9N (rs1801177) polymorphisms. RESULTS: The AG/GG genotype in D9N polymorphism was associated with higher LDL-C (low-density lipoprotein cholesterol) and lower HDL-C (high-density lipoprotein cholesterol) concentration. Significant interactions were found for D9N polymorphism and birth weight in association with plasma HDL-C concentration, and also for D9N polymorphism and BMI in association with plasma triglyceride (TG) and HDL-C levels. HindIII polymorphism had significant association with birth weight for HDL-C concentration, and with BMI for TG and HDL-C levels. Significant interactions were found for S447X polymorphism and BMI in association with plasma TG and HDL-C concentrations. CONCLUSION: We found significant interactive effects from LPL polymorphisms and birth weight on HDL-C concentration, and also effects from LPL polymorphisms and BMI on TG and HDL-C concentration.